2023
DOI: 10.4093/dmj.2022.0420
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Management of Patients with Diabetes and Heart Failure: A Korean Diabetes Association and Korean Society of Heart Failure Consensus Statement

Abstract: Diabetes mellitus is a major risk factor for the development of heart failure. Furthermore, the prognosis of heart failure is worse in patients with diabetes mellitus than in those without it. Therefore, early diagnosis and proper management of heart failure in patients with diabetes mellitus are important. This review discusses the current criteria for diagnosis and screening tools for heart failure and the currently recommended pharmacological therapies for heart failure. We also highlight the effects of ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 108 publications
0
3
0
Order By: Relevance
“…The overall prevalence of HF in South Korea is increasing, and reached 2.2% in 2018, 26 which was similar to that reported globally 27,28 . Approximately 30%‐40% of patients with diabetes have HF, 26 that is, people with diabetes are at a high risk of developing HF and, in most cases, exhibit no typical symptoms or signs 29,30 . Most cardiovascular outcome trials (CVOTs) have confirmed that DPP‐4 inhibitors are safe in terms of the risk of cardiovascular events, but a concern about the risk of HF was raised by the SAVOUR‐TIMI53 study (saxagliptin) and the EXAMINE study (alogliptin) 7,8 .…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The overall prevalence of HF in South Korea is increasing, and reached 2.2% in 2018, 26 which was similar to that reported globally 27,28 . Approximately 30%‐40% of patients with diabetes have HF, 26 that is, people with diabetes are at a high risk of developing HF and, in most cases, exhibit no typical symptoms or signs 29,30 . Most cardiovascular outcome trials (CVOTs) have confirmed that DPP‐4 inhibitors are safe in terms of the risk of cardiovascular events, but a concern about the risk of HF was raised by the SAVOUR‐TIMI53 study (saxagliptin) and the EXAMINE study (alogliptin) 7,8 .…”
Section: Discussionmentioning
confidence: 60%
“…27,28 Approximately 30%-40% of patients with diabetes have HF, 26 that is, people with diabetes are at a high risk of developing HF and, in most cases, exhibit no typical symptoms or signs. 29,30 by the SAVOUR-TIMI53 study (saxagliptin) and the EXAMINE study (alogliptin). 7,8 Although a causal relationship is unclear and has not been observed in other CVOTs of DPP-4 inhibitors, the use of DPP-4 inhibitors requires caution for patients who have, or are suspected of having, impaired cardiac function.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of comorbid diabetes mellitus (DM) in HF patients is 20–36% in Korea and 25–45% in Western countries [ 3 , 67 ]. Managing DM is crucial in HF patients [ 68 ].…”
Section: Special Consideration For Specific Comorbiditiesmentioning
confidence: 99%
“…Despite the dramatic improvement in short-and long-term outcomes of HF with established guideline-directed medical therapy, HF remains a significant health burden worldwide with increasing prevalence [9][10][11][12][13]. Current HF guidelines emphasize the importance of individualized assessment and management according to HF phenotypes [14][15][16].…”
Section: Introductionmentioning
confidence: 99%